Pergeseran Budaya Masyarakat Perlak Asan: Studi Kasus tentang Pakaian Adat - Nasruddin AS (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
The shift of traditional clothing in society is very common to happen because of an attempt to adapt with new need. The happening of shift in traditional clothing of marriage in Perlak Asan village, Sakti Sub-dis- trict, Pidie Regency focus more on the clothes during religious rite and cultural rite of marriage. This research is using qualitative method which is observation, interview and documentation. The result of research show that traditional clothing for marriage is changing from traditional into modern. But the shift is about the mod- ernization of the clothes which show the process of social culture transformation as the urge of society to be up to date with global world. Traditional clothing that is being used consists of values or messages that want to be delivered by the brides. Traditional clothing for example is Acehnese clothing, Seloyor. And modification of modern clothing is Acehnese clothing Duyung, Indian wedding dress, Barbie dress, Kebaya gown and Kebaya robe.